Mailed dosimetric audit of therapeutic proton beams using thermoluminescence MTS-N (LiF:Mg, Ti) powder – First results. (November 2017) - Kunst, J.; Kopeć, R.; Kukołowicz, P.; Mojżeszek, N.; Sadowski, B.; Stolarczyk, L.; Ślusarczyk-Kacprzyk, W.; Toboła, A.; Olko, P.
Abstract: Institute of Oncology in Warsaw provides mailed dosimetric service of radiotherapy units in Poland according to the procedure implemented by IAEA. The service applies the dosimetric thermoluminescence (TLD) system with detectors in form of capsules filled with MTS-N (LiF: Mg, Ti) powder. In these studies dosimetric properties of the TLD system were determined to adapt it for mailed dosimetric audits of proton radiotherapy units. Dose response of TLD capsules filled with MTS-N powder was studied for doses between 1.75 Gy and 2.25Gy in the middle of 5 × 10 × 10 cm 3 Spread Out Bragg Peak (SOBP). The SOBP was located at the different position (depth) in the water phantom in order to determine the energy dependence of the system. All exposures were performed at the isocentric gantry with Pencil Beam Scanning field at the Bronowice Cyclotron Center, Institute of Nuclear Physics (IFJ PAN). It was found that for TLD system with MTS-N powder the correction for the supralinear dose response should be applied for doses exceeding 2 Gy. No significant influence of response on the position (depth) of SOBP was observed. The preliminary results show that the standard mailed TLD dosimetry system based on MTS-N (LiF:Mg, Ti) can be adapted for auditing proton radiotherapy units. Highlights: A setup for auditing proton radiotherapy beams was proposed. An expression for the dose correction factor was found. Results show that the existing TLD mailed dosimetry audit system could be applied for auditing proton radiotherapy beams.